Marketing Communication Strategy For New Student Registration - Andreas Eko Soponyono; Anggoro Santoso; Muhammad Nur Ichsan (UniSadhuGuna Business School, 2024)
SMA ABC Bandung is a Collaborative Education Unit school with the largest number of competitors and is ranked second in West Java, has experienced an increase in the number of new student admissions, and has an international curriculum. The purpose of this research is to find out an overview of the marketing communication strategies used in recruiting new students. The research method used is a qualitative method with a descriptive approach, where the research informants are marketing communications staff, new students and parents. The impact of the marketing communication strategy used by SMA ABC Bandung on new student admissions can be analyzed based on several aspects. Through advertising on various platforms such as billboards, banners, radio, and social media channels such as Instagram and Facebook, the school is likely to increase awareness among the target audience about its offerings and educational programs. Sales promotions such as discounts on School Operational Assistance (SPP), Development Funds (DPP), referral programs, and scholarships are likely to encourage enrollment, attracting students who may have considered other options due to financial constraints. Based on the research discussion, it can be concluded that the marketing communications strategy carried out by SMA ABC Bandung during the researcher's research period in recruiting new students through a marketing communications mix included advertising, sales promotions, public relations, direct marketing and personal sales. Advertising is carried out through billboards, banners, billboards, radio, Instagram partner media, Facebook ads, Instagram ads, Google ads. Sales promotions provided include tuition discounts, DPP, referral programs, and 100% scholarship channels. Public relations activities carried out include Road to Give Bandung 2023. Direct marketing is carried out via email, WhatsApp and telephone. Personal Selling is carried out during Open House events, exhibitions at PVJ and Ciwalk, as well as online consultations